Availability of Infrastructure for Poverty Reduction in Indonesia: Spatial Panel Data Analysis - Galih Pramono; Waris Marsisno (Institute for Economic and Social Research, 2018)
Poverty is a key issue in various developing countries, including Indonesia. One of the efforts to reduce poverty is building the infrastructure. Therefore, this study aims to determine the effect of infrastructure on the level of poverty by considering the spatial effect in the period 2011–2015. This study applies spatial panel data analysis with Spatial Autoregressive (SAR) model with fixed effect. The findings show that the infrastructure of electricity, health, sanitation, and building of senior high school has a significant negative impact on the percentage of the underprivileged people. Meanwhile, the building of elementary school has a significant positive impact on the percentage of the underprivileged people.